Diagenetic alteration of benthic foraminifera from a methane seep site on Vestnesa Ridge (NW Svalbard). (May 2017) - Schneider, Andrea; Crémière, Antoine; Panieri, Giuliana; Lepland, Aivo; Knies, Jochen
Abstract: Anomalously low δ 13 C values in foraminiferal calcite tests are due to diagenetic alteration in methane seep sites. Our study applies diagenetically altered fossil benthic foraminiferal tests as geochemical tracers in reconstructing natural past methane seepage episodes at Vestnesa Ridge offshore NW Svalbard. We combine examinations of the test wall microstructure, mineralogical and stable carbon isotope composition of foraminifera and co-occurring authigenic carbonate nodules. We present a classification of visual and mineralogical characteristics of the exterior and interior test wall microstructure of the benthic foraminiferal species Cassidulina neoteretis having experienced different degrees of diagenetic alteration during methane seepage. Carbonate nodules comprising high-Mg calcite cement with 13–15 mol% MgCO3 have δ 13 C values as low as −32.3‰, which is consistent with a methane-derived origin. The visual, mineralogical and stable isotope investigations of C. neoteretis indicate a variable degree of diagenetic alteration and show δ 13 C values between −0.6 and −16.9‰. The negative δ 13 C values in benthic foraminifera are largely caused by precipitation of isotopically light methane-derived authigenic carbonate as high-Mg-calcite coatings, whose relative contribution to the bulk foraminiferal carbonate is estimated to be up to 58 wt%. Another key finding is the identification of the first seepage episode concurrent with Heinrich Event 1 (HE 1), and a second seepage episode at the onset of the Bølling-Allerød Interstadial. Highlights: Diagenetically altered foraminifera can be used as a tracer for methane seepage. The degree of diagenetic alteration displays variable methane seepage intensity. Diagenetically altered foraminifera report two seepage episodes (HE1; Bølling-Allerød). Seepage during HE1 lasted longer than previously constrained.